Implementasi Kebijakan Penanggulangan Perdagangan Wanita - Hetty Antje Geru (JIANA ( Jurnal Ilmu Administrasi Negara ), 2012)
The aim of this study is to have aview of the implementation of the policy regarding women trafficking in the North SulawesiProvince. The method of the research through a qualitative approac, which is case study, throughin-depth interview, focus group discussion, observation as well as study of related documents,victims story and triangulation. The studies shows that the implementation of women traffickingpolicy covered the content of the policy and the context of the implementation. Based on theexploration of the both factors , in fact that the implementation of local policy on women traffickingis working, although it didn’t achieve as it is expected yet. The role of politics appearence sodominance influence the process, causes so many constrain in the program so far.